ANALISIS KANDUNGAN TIMBAL (Pb) DAN LAJU KONSUMSI AMAN PADA KEPITING BAKAU (Scylla serrata Forskal) DI SUNGAI DONAN CILACAP - Nindita Purnamasari, Viola; Widiyanto, Agnes Fitria; Kuswanto, Kuswanto (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2014)
ABSTRACTWaste from the activities around the Donan River can contain heavy metals (lead) that can go into the water biota (Mangrove Crab), and enter the human body through contaminated food absorption. The maximum limit of Pb contamination in the Crab is 0.5 ppm, if it exceeds the maximum levels will endanger health. The study aims to determine the content of Lead on Mangrove Crab and sediments in the Donan River Cilacap and the safe consumption rate. This type of research that is descriptive study, with sampling methods that used is purposive sampling. Samples taken from three stations, with 4 replications at high tide and low tide. The results obtainedon the Pb content of sediment in Donan River Cilacap ranged from 1.187 to 40.555 ppm with an average of 7.629 ppm. The content of Pb in the mangrove crab in Donan River Cilacap ranged from 4.735 to 448.611 ppm with an average of 61.808ppm. The content of Pb in all the stations have exceeded the maximum limit of heavy metal contamination in the food that is equal to 0.5 ppm.Keywords : Lead, Mangrove Crab, Safe Consumption Rate, Donan River Kesmasindo, Volume 6, (3) Januari 2014, Hal. 157-165